2022
DOI: 10.3390/insects13070576
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insect Flour on Sourdough Fermentation-Fatty Acids, Amino-Acids, Minerals and Volatile Profile

Abstract: Acheta domesticus (L.1758) has been recently accepted by the European Union as a novel food, being the third insect that has been approved for human consumption. Nowadays, researchers’ attention is focused on exploiting new protein sustainable sources, and, therefore, insect flour has gained more and more interest. Organic acids, fatty acids, amino acids, aroma volatile compounds, and minerals were analyzed through HPLC-RID (High-performance liquid chromatography), GC-MS (Gas chromatography-mass spectrometry),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…Similar results were reported by Roncolini et al (2019) [ 16 ], who observed that a 5 to 10% addition of mealworm flour to wheat flour positively influenced bread volume. Vasilica et al (2022) [ 23 ] described that edible insect meal can function not only as a nutritional enhancer for a wide range of food products but can also support the development and growth of certain bacterial strains, for example Lactobacillus plantarum . Naturally occurring lactic acid bacteria are an important part of the microbial ecosystem in bread sourdough [ 24 ], and enhancing their viability by the addition of edible insects could be also beneficial for the fermentation process itself.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Roncolini et al (2019) [ 16 ], who observed that a 5 to 10% addition of mealworm flour to wheat flour positively influenced bread volume. Vasilica et al (2022) [ 23 ] described that edible insect meal can function not only as a nutritional enhancer for a wide range of food products but can also support the development and growth of certain bacterial strains, for example Lactobacillus plantarum . Naturally occurring lactic acid bacteria are an important part of the microbial ecosystem in bread sourdough [ 24 ], and enhancing their viability by the addition of edible insects could be also beneficial for the fermentation process itself.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat flour (WF) type 550 was purchased from Auchan supermarket in Timisoara, Romania. Based on the literature studies [ 7 ] and our own experience on obtaining flour composites [ 16 , 17 , 18 , 19 ], three types of flour composites were obtained: WFL10 (10% lupin flour and 90% wheat flour); WFL20 (20% lupin flour and 80% wheat flour); and WFL30 (30% lupin flour and 70% wheat flour).…”
Section: Methodsmentioning
confidence: 99%
“…The fourth cluster contained bars with buffalo worm flour, which are characterized by a pronounced sour taste. The observed relationship between increases in sourness, sweetness, bitterness, and saltiness and the fortification of bars with insect flour may be related to their high protein, mineral, and organic acid content [ 6 , 31 ]. Therefore, the results of the current study indicate that the amount and type of ingredients used in the production of bars may affect their organoleptic properties.…”
Section: Resultsmentioning
confidence: 99%